Digital image filters are not necessarily related to improvement in diagnostic of degenerative bone changes in the temporomandibular joint on cone beam computed tomography (Research, Society and Development, 2021)
This study assessed whether the use of digital image filters influences the detection of temporomandibular joint (TMJ) bone changes on cone beam computed tomography (CBCT). Two radiologists evaluated the TMJ images of CBCT scans to verify the presence of osteophytes, erosions, pseudocysts, bone sclerosis and flattening, using the software XoranCAT®; each image of the TMJ was assessed with and without the use of the following filters: Angio Sharpen 3x3 and Angio Sharpen 5x5. Kruskal-Wallis’ test was used to assess whether the application of filters influenced the scores assigned to the degenerative bone changes in the condyle. Flattening was present in 15 cases (51.72%), followed by osteophytes in six cases (20.69%), sclerosis in three cases (10.34%), and erosion in three cases (10.34%), with pseudocyst found in two cases (6.90%). No statistically significant difference was found in the scores (P = 0.786) regarding the original images and those treated with both filters. Digital image filters used in our study did not influence the diagnosis of degenerative bone changes in the TMJ on CBCT images.